Characteristics of law enforcement agencies in the field of water resources use (Journal of actual problems of jurisprudence, 2023)
In this article, we consider the favorable characteristics of the use of Water Resources. In the article, the author analyzed the current problems of law enforcement, which arise in connection with the use of Water Resources in the Republic of Kazakhstan, paid attention to the law enforcement and criminological aspects of law enforcement, related to these resources. The purpose of the scientific article is an exhaustive study of the specifics of the qualification of the law on regulation, closure or establishment of water and regulation of the sea environment, prescribed in the current law. If you consider the theoretical and practical significance of this article, you can consider the inclusion in the theory of co-operation of the right of basic income and recommendations, which reveal the essence of the right of Water Resources in the domestic law the law provides for the use of Water Resources, the adoption and improvement of regulated norms provided for by the code of the Republic of Kazakhstan. A special importance in the Prevention of corruption in this sphere is the consideration of issues related to environmental, law enforcement and legislation related to the protection of water. In the quality of research methods, logical-legal, systematic, functional, and comparative-legal methods were used. The scientific New Year is a comprehensive study of the problem of water safety, preventive activities of law enforcement and Natural Resources bodies in the field of water safety. Key words: water, water resources, pollution, pollution of water, flooding of water, establishment, sea environment.